Services-oriented learning commons model for public libraries - Mondejar, Liafeil C.; Esposo-Betan, Sharon Maria S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2016)
The never ending advances and changes both in technology and learning methods prompted the development of a new library model more commonly known as Learning Commons for academic libraries and school libraries. The implementation of this new model revitalized the libraries, increasing their relevance and solidifying its role within the academic community. This study sought to determine the feasibility of applying this model in public libraries to help strengthen its relevance to its community. A model containing five fundamental characteristics for the academic library Learning Commons was used as basis for this study. Each characteristic is composed of elements defining the model. This model was tested in terms of applicability to public libraries through the employment of a survey. Forty respondents from five city public libraries in Metro Manila rated each element according to the degree of its relevance and applicability to the public library.
The findings of this study resulted in a Learning Commons model for public libraries with four fundamental characteristics: 1) IT infrastructures, 2) librarian skills, 3) space and design, and 4) services. The characteristic collaborative learning included in the academic library Learning Commons was not included in the model due to its low relevance and applicability rating.
The IT infrastructure elements included are internet connection, computer terminals, printers, scanners and copiers, interactive board/smartboard, file storage/servers, audio/video conferencing services, and technology to boost teaching and learning together.
The librarian skills elements included and designing literacy programs and projects to assist patrons in using library services skills to better connect with users, research skills to assist users in their inquiries, IT skills for maintaining the library network facilities, basic IT skills such as computer functions and library network to assist students in using IT services, IT skills such as developing in-house information services, ability to develop collaboration with other discipline professionals, ability to recognize when information is needed and locate and evaluate said information, and finally, marketing ability to promote the Learning Commons.
The space and design elements included are computer workstations designed for team work, ergonomic and comfortable seating, flexible furniture arrangement that can be easily rearranged depending on user needs, exhibit or display areas, welcoming and inspiring entrance space, adaption of design principles such as practicality and sustainability, functional and aesthetically- pleasing facility, color, theme and lighting as design considerations.
The services elements included are library website with portals at the library collection, tutorials on how to use the technologies in the library, roaming IT specialist to assist users, information literacy classes, self-help materials for research, service desk staff to assist user concerns, e-databases and digital resources, equipment such as laptops, digital camcorders, digital camera, and flash drives, and collaborative workstations.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Information commons -- Philippines -- Manila Metropolitan Area..; Public Libraries -- Reference services -- Philippines